Visceral sensation and emotion: a study using hypnosis - Houghton, L A (BMJ Group, 2002)
Background and objectives: We have previously shown that hypnosis can be used to study the effect of different emotions on the motility of the gastrointestinal tract. These studies demonstrated that both anger and excitement increased colonic motility while happiness led to a reduction. The purpose of this study was to investigate the effect of hypnotically induced emotion on the visceral sensitivity of the gut. Methods: Sensory responses to balloon distension of the rectum and compliance were assessed in 20 patients with irritable bowel syndrome (IBS) (aged 17–64 years; 17 female) diagnosed by the Rome I criteria. Patients were studied on four separate occasions in random order either awake (control) or in hypnosis, during which anger, happiness, or relaxation (neutral emotion) were induced. Results: Hypnotic relaxation increased the distension volume required to induce discomfort (p=0.05) while anger reduced this threshold compared with relaxation (p<0.05), happiness (p<0.01), and awake conditions (p<0.001). Happiness did not further alter sensitivity from that observed during relaxation. There were no associated changes in rectal compliance or wall tension. Conclusions: Further to our previous observations on motility, this study shows that emotion can also affect an IBS patient’s perception of rectal distension and demonstrates the critical role of the mind in modulating gastrointestinal physiology. These results emphasise how awareness of the emotional state of the patient is important when either measuring visceral sensitivity or treating IBS.